2011
DOI: 10.1093/cid/cir524
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cognitive Impairment in Human Immunodeficiency Virus

Abstract: Recent publications estimate the prevalence of human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) exceeds 50%, and this rate is likely higher among older patients. Cognitive impairment may impact medication adherence, and symptomatic impairment has been linked to all-cause mortality providing some impetus for early detection. There are currently insufficient data to inform solid recommendations on screening methods. Most HIV-specific tools have poor performance characteristics for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 36 publications
(41 reference statements)
1
93
0
Order By: Relevance
“…11 The Montreal Cognitive Assessment (MoCA) more broadly evaluates domains known to be affected by HIV and has sensitivity for the detection of Mild Cognitive Impairment (MCI) and milder Alzheimer's disease in the general population. 12 The few studies that have examined the utility of the MoCA in an HIV population show promise; but, to date, none have examined performance in a sample of elder people with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…11 The Montreal Cognitive Assessment (MoCA) more broadly evaluates domains known to be affected by HIV and has sensitivity for the detection of Mild Cognitive Impairment (MCI) and milder Alzheimer's disease in the general population. 12 The few studies that have examined the utility of the MoCA in an HIV population show promise; but, to date, none have examined performance in a sample of elder people with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it is particularly worrying that HIV-infected patients remain at significant risk of depressive symptoms and neurocognitive impairment, factors that may interfere with adherence to HAART (Hinkin et al, 2004;Valcour et al, 2011), significantly affect quality of life (Parsons et al, 2006;Osowiecki et al, 2000;Tozzi et al, 2004), and may hasten progression to AIDS. Accordingly, these results underscore the importance of early diagnosis and monitoring of depressive symptoms in this vulnerable population.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, more recent research efforts with other language groups have made substantial progress. For example, Valcour, Paul, Chiao, Wendelken, and Miller (2011) have an excellent review of screening measures for HAND in aging HIV-positive cohorts. In addition, Overton et al (2013) found that the Montreal Cognitive Assessment (MoCA) and the Alzheimer's Disease (AD-8) screening tools correlated with formal neuropsychological testing in an HIV-positive sample, but reported that the sensitivity and specificity of these instruments were moderate in predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%